The Arts and Crafts of Literacy. Islamic Manuscript Cultures in Sub-Saharan Afric - Nobili, Mauro; Brigaglia, Andrea (De Gruyter, 2017)
During the last two decades, the (re-)discovery of thousands of manuscripts in different regions of sub-Saharan Africa has questioned the long-standing approach of Africa as a continent only characterized by orality and legitimately assigned to the continent the status of a civilization of written literacy. However, most of the existing studies mainly aim at serving literary and historical purposes, and focus only on the textual dimension of the manuscripts. This book advances on the contrary a holistic approach to the study of these manuscripts and gather contributions on the different dimensions of the manuscript, i.e. the materials, the technologies, the practices and the communities involved in the production, commercialization, circulation, preservation and consumption. The originality of this book is found in its methodological approach as well as its comparative geographic focus, presenting studies on a continental scale, including regions formerly neglected by existing scholarship, provides a unique opportunity to expand our still scanty knowledge of the different manuscript cultures that the African continent has developed and that often can still be considered as living traditions.
English
Keywords: manuscript; Islam culture; Subsahara